Design of an LMS-mediated tutorial to support deep and effective engagement in the process of learning mathematics - Kigundu, Stephen (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
Many institutions of Higher Learning have adopted a variety of Learning Management Systems (LMS) as platforms for e-learning implementation. However, the design and nature of LMS technologies present challenges to the design of LMS-based activities that engage students in learning to do mathematics. There are no clear guidelines or strategies for designing LMS-based activities that engage students in complex mathematical processes. Hence, using technologies in mathematics education often replicates instructivist positions and practices. Conversely, using constructivist principles, modes of mathematical engagement, and e-learning tools to mediate learning provides an integrated framework to transform the use of an LMS as a platform for e-learning implementation and promote deep engagement in mathematical learning. The objective of this study was to explore mechanisms that could be useful for conceiving activities to support the learning of Mathematics using an LMS-mediated tutorial. The design, redesign and evaluation of the e-tutorial are reported upon. In preparation for the study, an LMS-based tutorial was designed and developed to be used as a test-bed to investigate how these e-learning tools could support learning to do mathematics. A Trigonometry module, consisting of course content in the form of resources and tasks to help the students to explore, practice and apply right triangle concepts, was used to investigate and derive design strategies. A mixed method research approach with a reflexive self-study research design was used. A group of first-year university student volunteers studying mathematics in the mechanical engineering department were used to test the tutorial. The students were asked to do a series of tasks using the e-learning environment during the Mathematics tutorial period. Data was collected using in-class observations, interviews, screen capture videos, student-written responses, and system-generated data. All students were encouraged to complete a learning journal detailing their experiences during the tutorial using an LMS-based tool. The students were given no training, but a tutor (researcher) was available to answer any questions they may have had. Contradiction analysis was used to evaluate the data, compare purpose and practice and judge whether the activity or tool was fitted for the intended purpose. Findings were in the form of transformations of the e-tutorial system as it was developed. Among the most noteworthy contributory modifications were changing from 1) "read first, then do" to "do first, read when necessary" , 2) "work on the computer" to "work on paper then capture on the computer" , 3) "physically separated work with computer-enabled social contact" , to "individual computer work in face-to-face social settings." 4) "single-level of resource provision" to "multi-level, demand-driven resource provision" and 5) "self-regulated" learning process regulation to "computer-assisted" learning process regulation. The discussion of these findings indicated that to enable students' deep and effective engagement in the process of learning fundamental trigonometry within an LMS-mediated tutorial, one needs to design the system with some activities that can create a demand for knowledge, encourage rough work and face-to-face social interaction, supported by multi-level, demand-driven resources, and computer-assisted learning-process regulation. Contributions to research by this study were in the form of 1) Design Principles for LMS-mediated tutorials, 2) Principles for an e-tutorial development methodology, and 3) The LMS-mediated tutorial system.
Keywords: Learning Management Systems (LMS); e-learning; Educational technology; Mathematics-- Study and teaching (Secondary); Constructivism (Education); Mixed methods research